EVALUATION OF THE MERDEKA LEARNING PROGRAM AT MERDEKA CAMPUS WITH DISCREPANCY EVALUATION MODEL (STUDENT PERSPECTIVE) - Pandu Adi Cakranegara; Donald Samuel Slamet Santoso (Sean Institute, 2022)
This study aimed to evaluate the implementation of the Merdeka Learning program at the Merdeka Campus. The program evaluation research carried out adopted the discrepancy evaluation model. Research data in quantitative and qualitative were collected utilizing questionnaires, interviews, and documentary studies. The respondents of this study were students from 3 universities in West Java, Central Java, and West Kalimantan. The data is then analyzed for gaps with the expected targets or achievements. The results of this study indicate that the Independent Campus Independent Learning Program is viewed in various ways by students. The student group consists of three categories: students who view college as a means to achieve goals, students who view college as a means for self-development, and students who view college as a temporary solution. These three groups of students have different perspectives on the MBKM program in terms of interest, institutional support, and learning impact. In general, the MBKM program has been implemented by exceeding the targets expected in this study.